Effect of Unauthorized Addition of Storeys in a Residential Building - Ghimire, Meer Raj; Thapa, Krishpa; Gorkhali Shrestha, Aadeep; Dhami, Chandra Bahadur; Paudel, Chetnath; Bajracharya, Sanjeema (Journal of Science and Engineering, 2026)
In Nepal, it has become common practice to add stories and projections, without legal authorization and proper design for these extensions, which has led to much damage as observed in the recent 2015 Gorkha earthquake. Therefore, this paper studies the effect of unauthorized addition of storeys by FE modelling using response spectrum method. Two cases were considered: (1) replication of a typical storey until structural failure, (2) incorporation of 1-ft, 2-ft, and 3-ft extensions along with stepped projections, followed by vertical replication until failure. The study found that base shear and storey drift at the top storey increased with the addition of the first storey due to increased seismic mass but gradually decreased as more storeys were added. The ground and first floors were found to be most vulnerable to structural failure due to unauthorized addition of storeys particularly in cases coupled with horizontal extensions.